Fungsi Sosial-Kultural Sastra: Memajukan Kebudayaan dan Mengembangkan Peradaban - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
There are three important social-cultural functions of literary works. First, the assumption that literary work is at the same level as the work of a priest or prophet. Second, the notion that the most important thing for the literary work is entertains. Third, the assumption that literary works should teach something with using entertaining system. The linkage of literary works to social-cultural systems can be further known by studying the value of relationships in literary works with the value of system in society. The value in literature is the system of social norms imposed in literary works, and the value of system in society is the norm system prevailing in the daily life of society. Ideally literary works should bring innovation, means renewal to the society. Therefore, the deviations of values in literary works do not imply the defiance of the standard conventions of social norms. Such deviations signify the creation of cultural dynamics, the establishment of new values. At the same time its open opportunities for people to move continuously, reconstructing thought to become more critical, analytical, and humanistic.